MDE‐based process tailoring strategy. Issue 4 (8th January 2013) - Hurtado Alegría, Julio A.; Bastarrica, María Cecilia; Quispe, Alcides; Ochoa, Sergio F.; Raffo, David; Pfahl, Dietmar; Zhang, Li
SUMMARY Defining organizational software processes is essential for enhancing maturity because they cannot be improved if they are not specified. However, software process definition is hard and still not good for assuring productivity because the best process depends on the project's particularities. The process engineer can define a specific process for each kind of project, but this is expensive, unrepeatable, and error prone. Moreover, it is difficult to foresee all project scenarios and therefore the appropriate processes. The most usual situation is to apply always the same software process, although it is known to be suboptimal. To deal with this challenge, we propose a model‐based approach to software process tailoring that automatically generates project‐specific processes on the basis of the organizational process and project contexts. We still require competent process engineers to define the company's process, but once done, our approach is systematic, repeatable, and easy to use. The proposal is applied for tailoring the requirements engineering process of a medium‐size Chilean company. Processes obtained matched those used in the company for planned project contexts, and they were also reasonable for nonexpected situations. The company's process and project engineers agreed that the approach was highly valuable. Copyright © 2013 John Wiley & Sons, Ltd.